A Case of Acute Co‐infection with Human Immunodeficiency Virus and Cytomegalovirus. (27th March 2015) - Hadano, Yoshiro; Shirano, Michinori; Kameda, Kazuaki; Goto, Tetsushi
Abstract : Acute human immunodeficiency virus (HIV) infection refers to the period of primary HIV infection in which there is viral replication, viremia, and variable non‐specific symptomatology consistent with an acute viral syndrome. Although HIV infection may occur at the same time as other sexually transmitted infections such as chlamydia, gonorrhoea and syphilis, co‐infection with HIV and cytomegalovirus (CMV) is however rare. We report a 25‐year‐old man who presented with fever and headache, and who was diagnosed with concurrent HIV‐1 and CMV infection. His condition improved after hospital day 10 without specific treatment. It is important to understand that a number of viruses can cause an infectious mononucleosis‐like syndrome and aseptic meningitis, including HIV.